A COMPARISON OF BRIEF FUNCTIONAL ANALYSES WITH AND WITHOUT CONSEQUENCES. (18th October 2012) - Call, Nathan A.; Zangrillo, Amanda N.; Delfs, Caitlin H.; Findley, Addie J.
<x xml:space="preserve">Abstract</x> Variations to traditional functional analysis methodology, such as brief functional analyses (BFAs), are prevalent in the literature. In the current evaluation, two types of BFAs were each conducted with five participants. In one, potential motivating operations (MOs) were presented, and problem behavior resulted in delivery of an associated consequence. In the other, the same MOs were presented, but no consequences were delivered. Results of the two BFAs were compared with respect to the conditions in which problem behavior occurred and the degree of differentiation between test and control conditions. Results across the BFA methodologies generally matched across all five participants. However, greater differentiation was observed in the BFA that did not include consequences. Copyright © 2012 John Wiley & Sons, Ltd.